(untitled) - Susmita Hazarika (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Inclusive education is a structure or system of education in which special children with special need are signed up in normal classes and are provided supportive special services. With the spreading worth of equal and tantamount opportunities for education for all, inclusive education is becoming as one of the significant and notable aims of schools. It aims to include students with special needs in the same and regular classrooms as well as to provide equal social rights to them like other general students. The notion of attitude is mainly concerned with the thinking ways, acting and behaving of an individual towards a particular thing which is built as an outcome some kind of learning experiences. The present study was an attempt to identify the level of attitude of high school teachers towards inclusive education. The sample of the study comprised of 200 high school teachers of Amguri education block under Sivasagar district out of which 100 are male and 100 are female. Here, purposive sampling technique was incorporated to select the necessary sample high schools. An attitude scale namely Teacher Attitude Scale Towards Inclusive Education (TASTIE) standardized and validated by Dr. Vishal Sood and Dr. Arti Anand was administered to collect data. Statistical techniques such as mean, median, mode, S.D., were calculated to analyze and interpret the data. The study revealed that the high school teachers of Sivasagar district have a positively high attitude towards inclusive education.